2019
DOI: 10.1007/s13205-019-1773-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and 3D model of a fatty-acid elongase in a carnivorous freshwater teleost, the European perch (Perca fluviatilis)

Abstract: The European perch (Perca fluviatilis) is a carnivorous freshwater fish able to metabolise polyunsaturated fatty acids (PUFA) into highly unsaturated fatty acids (HUFA). This makes it a potential candidate for sustainable aquaculture development. In this study, special attention is given to the fatty-acid elongase (ELOVL) family, one of the two enzymatic systems implied in the HUFA biosynthesis. Structural information on European perch enzyme converting PUFA into HUFA is obtained by both molecular cloning and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…The secondary structures of these proteins in E. tetradactylum revealed 40.86-50.30% alpha helixes, 28.10-28.10% random coil, 13.75-20.67% extended strand and 2.38-4.47% beta turn, while these ratios were predicted to be 47.55-53.27, 30.00-36.01, 6.99-18.12 and 2.38-4.75%, respectively, in E. rhadinum (Table 3). High ratio of alpha helixes and random coil in the Elovl protein structure might play important roles in fatty acids biosynthesis in fish, in accordance with the literature for the order Perciformes in Perca fluviatilis 36 . Additionally, the secondary structure pattern of Elovl proteins in the candidate E. tetradactylum and E. rhadinum species were highly similar (Fig.…”
Section: Evolution Of Divergence and Conservation Of Elovl Genes Dive...supporting
confidence: 90%
“…The secondary structures of these proteins in E. tetradactylum revealed 40.86-50.30% alpha helixes, 28.10-28.10% random coil, 13.75-20.67% extended strand and 2.38-4.47% beta turn, while these ratios were predicted to be 47.55-53.27, 30.00-36.01, 6.99-18.12 and 2.38-4.75%, respectively, in E. rhadinum (Table 3). High ratio of alpha helixes and random coil in the Elovl protein structure might play important roles in fatty acids biosynthesis in fish, in accordance with the literature for the order Perciformes in Perca fluviatilis 36 . Additionally, the secondary structure pattern of Elovl proteins in the candidate E. tetradactylum and E. rhadinum species were highly similar (Fig.…”
Section: Evolution Of Divergence and Conservation Of Elovl Genes Dive...supporting
confidence: 90%
“…INVSc1 containing pYES2/NT C-ELOs was incubated on SC-U for 48 h at 28 • C, diluted to an OD600 of 0.4, and then an equal amount was added to the induction medium. Cultivation conditions were maintained at 28 • C for 48 h. When needed, 100 µM fatty acid substrates (NU-CHEK, Elysian, MN, USA), including linoleic acid (LA, C18:2 ∆9,12 ), α-linolenic acid (ALA, C18:3 ∆9,12,15 ), γ-linolenic acid (GLA, C18:3 ∆6,9,12 ), arachidonic acid (ARA, 20:4 ∆5, 8,11,14 ), eicosapentaenoic acid (EPA, 20:5 ∆5,8,11,14,17 ), methyl arachidate (mC20:0), and 0.4% Tergitol NP-40 (Sigma, St. Louis, MO, USA, v/v) for fatty acid solubilization were added to the SC-U induction medium. The cultures were collected and the pellets were used for further analysis.…”
Section: Culture Conditionsmentioning
confidence: 99%
“…Fatty acid analysis of pY-PsELO revealed decreased C16:0 from 20.5% to 15.5%, and new peaks for C20:0 with 2.4% and C22:0 with 0.7% compared to control, suggesting PsELO can sequentially elongate C16:0 to longer chain fatty acids. PY-McELO fatty acid data showed that McELO could convert 8.4% of LA to C20:2 ∆11,14 and 3.2% of ALA to C20:3 ∆11, 14,17 . Quantification results suggested that PrELO elongated 78.…”
Section: Functional Analysis Of Mcelo Prelo and Pselo Genes In S Cere...mentioning
confidence: 99%
See 1 more Smart Citation
“…In fish, fads2 was responsible for introducing double bonds at specific positions of the fatty acyl chain [ 12 ]. The elovl gene family in fish includes multiple elovl genes such as elovl2 , elovl4 , and elovl5 , which have specific substrates in the elongation of PUFAs [ 13 ]. The SNPs in the coding and promoter regions of fads2 and elovl5 have been proven to be associated with the PUFAs content in human [ 14 ], beef cattle [ 15 ], bovine milk [ 16 , 17 ], pigs [ 18 ], and gilthead sea bream [ 19 ].…”
Section: Introductionmentioning
confidence: 99%